A Analisis ICT Literacy Siswa SMP Melalui Pembelajaran Lingkungan Konsumerisme Hijau Berbantuan Padlet - Novia Amarta Handayani; Dadan Rosana; Insih Wilujeng; Mega Indah Puspita Sari; Erfin Nofianti; Siti Fatimah Az-Zahro; Desi Ramadhanti (Jurnal Penelitian Pendidikan IPA, 2022)
Information and communication technology supports innovative learning and creates a learning environment to develop student competencies in the 21st century. Science learning that is integrated with ICT can equip students with ICT literacy as a provision for a future full of global competition. This study aims to analyze students' ICT literacy through learning the green consumerism environment with the help of Padlet. This study uses a quantitative descriptive method with a research sample of 32 students of grade VII SMPN 2 Bungkal taken by purposive sampling technique. Data collection techniques using interviews, questionnaires, and observation. Research instruments in the form of interviews, questionnaires, and observation sheets. The data analysis technique is a quantitative percentage to determine the category of students' ICT literacy. The results show that students' ICT literacy scores for each aspect are access 100% (very high), manage 96.88% (very high), integrate 87.5% (very high), evaluate 40.63% (very low), create 56.25% (low), and communicate 75.00% (medium). The average percentage of students' ICT literacy scores reached 76.06% in the high category. The results of this study can be used as a basis for developing integrated science learning materials with ICT to facilitate students' ICT literacy.